Understanding Multilingualism and Code-Switching among English Department Students Across Home, Campus, and Social Media - Maemuna Muhayyang; Andi Sukri Syamsuri; Muh. Fakhrul Armas; Nayla Putri Humairah; Nurmutya Annisa (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigates multilingualism and code-switching practices among English Department students across three communication domains: home, campus, and social media. Students in Indonesia regularly interact in multiple languages, Indonesian, English, and regional languages yet limited research explores how these linguistic resources are managed across different social contexts. This study aims to describe (1) how students employ multilingualism and code-switching in their daily communication, and (2) what factors influence their language choices across these domains. Using a descriptive qualitative design, data were collected through open-ended questionnaires and semi-structured interviews with undergraduate English Department students. Participants were selected through purposive sampling, and data were analyzed thematically to identify recurring patterns of language use and switching functions. Findings reveal that students display domain-dependent multilingual behaviour. At home, regional languages and Indonesian are dominant due to family norms and cultural identity. On campus, Indonesian is primarily used for peer interaction, while English appears in academic tasks and lecturer communication. On social media, students frequently mix Indonesian and English for stylistic purposes, identity expression, and wider audience engagement. Code-switching functions include clarifying meaning, maintaining conversational flow, expressing identity, and adapting to interlocutors. Language choice is further shaped by context, topic, proficiency, and social relationships. Overall, the study shows that students use their linguistic repertoire flexibly rather than separating languages into fixed systems. These findings contribute to understanding multilingual behaviour in higher education and highlight code-switching as a meaningful communicative strategy in academic and digital contexts.